Deconstruction-reconstruction : the experiential catalogue of time passes - Tan, Jenson Gabriel Hong Charn (Nanyang Technological University, 2021)
In line with the recent pandemic in 2020, physical visual art exhibitions have been translated online for the sake of social distancing and the prevention of intermingling. Due to time constraints from the urgency of the matter, many translations of physical to digital exhibitions are completed in haste, resulting in the loss of physical experience when viewing an exhibition.